Respuesta :

suspho

Answer:

in the picture

Step-by-step explanation:

in the picture

Ver imagen suspho

Answer:

6.4 = b     and     7.8 = a

Step-by-step explanation:

Using the formula:

a^2 + b^2 = c^2

we can find the length of b

for the first triangle

now we just plug in the lengths.

5^2 + 4^2 = b^2

simplify into :

25 + 16 = b^2

add

41 = b^2

now in order to get rid of the ^2, we just find the square root of 41.

√41 ≈ 6.4

6.4 = b

Now we just need to solve for A

since we know

a^2 + b^2 = c^2 that must mean

c^2 - b^2 = a^2

so this is the formula we will be using.

now we just plug in the lengths of the second triangle into this equation.

10.5^2 - 7^2 = a^2

simplifies into

110.25 - 49 = a^2

subtract

61.25 = a^2

now we just find the square root of 61.25.

√61.25 = 7.8

7.8 = a

you can check this by putting it back in the formula

a^2 + b^2 = c^2

I will do this quickly (only for the second triangle)

we know

a = 7.8

b = 7

c = 10.5

7.8^2 + 7^2 = 10.5^2

simplifys into

60.84 + 49 = 110.25

60.84 + 49 ≈ 110

110.25 ≈ 110

110 = 110

which proves that this is correct.

ACCESS MORE